EFFECTIVENESS OF ENVIRONMENT-BASED DIFFERENTIATED LEARNING DESIGN TO IMPROVE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Ronny Sitanggang; Dede Ruslan; Anita yus (Jurnal Ilmiah Teunuleh, 2022)
The purpose of this study is to determine the effectiveness of developing environmentally-based differentiated learning designs to optimize the needs and learning outcomes of elementary school students, Palipi District, Samosir Regency. This research was conducted in elementary school, Palipi district, Samosir regency. This research method is a development research from Thiagarajan. The subject of the study was a teacher in an elementary school in Palipi Subdistrict, Samosir District. The data analysis techniques in this study are descriptive studies and t-tests. The results of the research and conclusions in this study are that the learning tools developed have met the criteria for effectiveness, namely (1) the completion of classical student learning in small-scale trials has reached the good category and in large-scale trials has reached the excellent category; (2) the achievement of student learning objectives during learning activities that meet the ideal criteria set; (3) positive student responses to the components of learning tools and learning activities developed; and (4) the allocation of ideal use of time.